2011
DOI: 10.4049/jimmunol.1100269
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Analysis of the Human T Regulatory Population Uncovers Functional Heterogeneity and Instability within FOXP3+ Cells

Abstract: Natural FOXP3+CD4+CD25High regulatory T cells are critical in immunological self-tolerance. Their characterization in humans is hindered by the failure to discriminate these cells from activated effector T cells in inflammation. To explore the relationship between FOXP3 expression and regulatory function at the clonal level, we used a single-cell cloning strategy of CD25-expressing CD4+ T cell subsets from healthy human donors. Our approach unveils a functional heterogeneity nested within CD4+CD25HighFOXP3+ T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 61 publications
2
79
0
1
Order By: Relevance
“…[13][14][15] As naïve Treg cells are by definition not induced but of thymic origin, these observations suggest that human nTreg cells, like their murine counterpart, are more capable of maintaining their lineage than are peripherally induced, antigen-experienced iTreg cells. 3 Ex vivo, it has been shown that FOXP3 + Treg cells can exhibit a certain pluripotency, whereby they can co-express FOXP3 and inflammatory cytokines such as IFNc and/or IL-17.…”
Section: Introductionmentioning
confidence: 86%
“…[13][14][15] As naïve Treg cells are by definition not induced but of thymic origin, these observations suggest that human nTreg cells, like their murine counterpart, are more capable of maintaining their lineage than are peripherally induced, antigen-experienced iTreg cells. 3 Ex vivo, it has been shown that FOXP3 + Treg cells can exhibit a certain pluripotency, whereby they can co-express FOXP3 and inflammatory cytokines such as IFNc and/or IL-17.…”
Section: Introductionmentioning
confidence: 86%
“…Detection of Tregs based upon their positive expression of CD3, CD4 and CD25 and downregulated CD127 expression (rather than expression of the transcription factor, FoxP3), was based upon reports that FoxP3 expression may prove unreliable as a marker of human Tregs as it appears to define a number of functionally heterogeneous populations which differ in their suppressive function and activation status [30,31]. Tregs are proposed to play a role in the resolution of lung inflammation [32], and therefore it seems fitting that these cells are reduced during the acute inflammatory response alongside heightened neutrophilia and increased iPMLCs.…”
Section: Discussionmentioning
confidence: 99%
“…According to a number of studies, not all FOXP3+ T cells are functional Tregs, and it is possible to induce a portion of the Treg signature without the presence of FOXP3 [37,38] since activated human T cells express Foxp3 transiently without acquiring suppressor capacity [39,40] The essential aspect of the Treg cell (FOXP3 expression and suppressive capability) can be maintained in differing Treg sub-populations identified in various anatomical locations as well as under pathological conditions [41][42][43]. Their characteristics allow phenotypic/functional adaptation to block full immune responses.…”
Section: Treg Functionsmentioning
confidence: 99%